2021
DOI: 10.1007/s12032-021-01542-6
|View full text |Cite
|
Sign up to set email alerts
|

sABLATE: a simplified ABLATE score for prediction of complications and outcome in percutaneous thermal ablation of renal lesions

Abstract: To evaluate the performance of a simplified-ABLATE score (sABLATE) in predicting complications and outcome in respect to RENAL, mRENAL and ABLATE scores. MethodsThis study included 136 renal lesions in 113 patients (M:F ratio=2.5; mean age 70.8 years). 98 tumors underwent cryoablation at San Raffaele hospital between 01/2015 and 03/2020, 37 microwave ablation at San Paolo or Policlinico hospitals between 07/2016 and 03/2020. RENAL, mRENAL, ABLATE and sABLATE scores were calculated using preprocedural imaging. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In recent years, thermal ablation has been gaining popularity, and is now accepted as one of the treatment methods in SRMs, including successful treatment of obese patients and cystic lesions [3,[20][21][22][23]. Some authors reported comparable results of thermal ablation and NSS in selected patients [9,20,24].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In recent years, thermal ablation has been gaining popularity, and is now accepted as one of the treatment methods in SRMs, including successful treatment of obese patients and cystic lesions [3,[20][21][22][23]. Some authors reported comparable results of thermal ablation and NSS in selected patients [9,20,24].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the progress in imaging techniques and wide introduction of ultrasonography (US) and computed tomography (CT) imaging has led to an increased detection of renal tumours, including small renal masses (SRM, kidney tumours smaller than 4 cm) [1,2]. While surgery is still the standard of care, there is a growing interest in Cancers 2023, 15, 518 2 of 10 minimally invasive treatment, such as thermal ablation [3]. The efficacy of thermal ablation has already been demonstrated, especially in case of SRMs, it is preferred for patients with renal masses ≤3 cm with contraindications or unwillingness to undergo surgery, especially people who are elderly, or have comorbidity, with bilateral tumours, and solitary kidney [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations